Sosiopragmatik Imperatif Iklan pada Media Sosial - Indah Rahmayanti; Alvi Fajar (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2020)
This study aims to determine the imperative sociopragmatics form on social media ads Instagram, Facebook and Line published in April-May 2018. The method used in this study is a descriptive qualitative method. The results of the analysis of this study reveal that there are 41 imperative sociopragmatic forms of 30 advertisements used as imperative sociopragmatics analysis material on social media Instagram, Facebook, and LINE. The imperative sociopragmatics forms which have been analyzed are 19 advertisements in the form of imperative sociopragmatic, 2 advertisements in the form of imperative sociopragmatic demand, there are no ads in the form of imperative sociopragmatic licensing, 9 advertisements in the form of imperative sociopragmatic invitations, 11 advertisements in the form of imperative sociopragmatic orders. Based on the results of this analysis, it can be concluded that the form of sociopragmatics that often arises is ordinary sociopragmatics.